KONTRA MASYARAKAT TERHADAP MENINGKATNYA KRIMINALITAS PASCA ASIMILASI NARAPIDANA DAMPAK COVID-19 - Lila Afrida Pebriana (Legal Standing : Jurnal Ilmu Hukum, 2020)
Criminology is the study of crimes that occur in society. Crime is an act that causes harm to others, violates social norms and violates the law. Seen in a social context, it is a phenomenon that occurs without boundaries of time and space which is part of the concerns in society. This is also in line with the assimilation of prisoners on the pretext of minimizing the chain of the spread of Covid-19. This is a new concern in society as well as the public's perception that ex-convicts look badly so that society does not agree with the assimilation of prisoners. Therefore, the society's contra against the increase in crime after the assimilation of prisoners due to the impact of Covid-19 in Indonesia is due to social economic or educational factors that encourage someone to do evil. Every criminal act will be subject to a criminal sanction in accordance with the purpose of the law, namely protecting the public interest so that everyone who does evil will be punished for what he did.